2007
DOI: 10.1002/eji.200737126
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mouse CD4 T cell subsets defined by expression of KLRG1

Abstract: The mouse killer cell lectin-like receptor G1 (KLRG1) is an inhibitory receptor known to be expressed on a subset of NK cells and antigen-experienced CD8 T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 43 publications
3
59
0
1
Order By: Relevance
“…Thus, the canonical signature of bulk Treg cells, defined by us and others, is really a composite derived from cells of diverse subphenotypes. Certainly, there is precedent for the subphenotypes observed here, as variability in the surface expression of CD103, Klrg1, or Cxcr3 and corresponding functional diversity have been described previously (38)(39)(40)(41).…”
Section: Discussionsupporting
confidence: 61%
“…Thus, the canonical signature of bulk Treg cells, defined by us and others, is really a composite derived from cells of diverse subphenotypes. Certainly, there is precedent for the subphenotypes observed here, as variability in the surface expression of CD103, Klrg1, or Cxcr3 and corresponding functional diversity have been described previously (38)(39)(40)(41).…”
Section: Discussionsupporting
confidence: 61%
“…In addition to CTLA-4 and PD-1, expression of 4-1BB and KLRG1 has been associated with enhanced Treg function (17,18). In each case, we found that combination blockade of the CTLA-4 and PD-1 pathways significantly decreased the fraction of Tregs expressing the relevant activation marker (Fig.…”
Section: Combination Coinhibitory Receptor Blockade Decreases Expressmentioning
confidence: 62%
“…Furthermore, within the Treg population isolated from infected mice, cluster analysis revealed that exclusively 64 genes were upregulated and 50 genes were downregulated when compared with Tregs isolated from naive mice. Interestingly, within this cluster we did not find gene expression of classical Treg markers such as IL-10 or TGF-b, but rather granzyme B, secretory leukoprotease inhibitor 1 (Slpi), metallothionein-1 (Mt1) and killer cell lectin-like receptor G1 (Klrg1), effector molecules implied in the literature to be involved in regulating inflammatory processes (21)(22)(23)(24).…”
mentioning
confidence: 88%